The games as a pegagogical tool in the improvement of its teaching practice - Torres Murga, María Rosa (2020)
The objective of the research was to analyze how the game through its various methodological, playful and didactic strategies enable the development of the pedagogical practice developed by teachers of the initial level in the teachinglearning process. The methodology used was centered on the qualitative approach, based on interpreting the meaning of the actions carried out by the teachers using the semi-structured interview technique, whose instrument was the questionnaire based on open questions. The results showed that the teachers managed to improve their work at the pedagogical level and significantly after having been prepared and developing this strategy.